(untitled) - Kotler, Philip (New York, 1997)
The Marketing of Nations is the first book in its field to connect macroeconomic public policy with the microeconomic behavior of industries, firms, and consumers, and the first to apply strategic planning to the building of national wealth. Step by step, the authors show how managers, corporate strategists, and government policymakers and planners can determine the pathways that will best achieve economic development in the context of world markets. With plentiful case material on Japan, the Four Tigers, China, India, Southeast Asia, Latin America, and Eastern Europe, the authors provide the first comprehensive synthesis of economic, political, and cultural factors that affect economic progress in all nations, both industrial and developing.
Keywords: Economic development,Economic policy,Phát triển kinh tế,Chính sách kinh tế